The Mapping Students' Critical Thinking Ability on Vibration and Wave Material - Yuliastrin, Adisti; Vebrianto, Rian; Fiqri, Muhammad; Berlian, Mery (Universitas Muhammadiyah Sidoarjo, 2023)
Students' critical thinking skills are very important in facing the challenges of the 21st century. The purpose of this research is to determine the level of students' critical thinking. The benefit of this research is to obtain test results related to students' critical thinking abilities. The methodology in this study used a survey method involving 75 students who were taken randomly. The instrument used is in the form of critical thinking questions which are distributed via gform. The data obtained was analyzed using SPSS. Based on the survey results it is known that the number of subjects is 75 respondents consisting of 48 women and 27 men. Based on the survey results, it is also known that the average student's critical thinking skills are in the good category with a score that can be explained in detail, namely giving simple explanations (8.0), building basic skills (7.9), making inferences (7.8). provide further explanation (7.6) and set strategies and techniques in solving science questions (7.9). In conclusion, the construct that has the highest average value is to provide a simple explanation with an average value of 8.0 and the lowest is to provide a further explanation of 7.6. The recommendation from this study is that students' critical thinking skills still need to be improved and teachers can use the instruments that have been used.